A High Oat-Bran Intake Does Not Impair Zinc Absorption in Humans When Added to a Low-Fiber Animal Protein-Based Diet - Sandström, Brittmarie; Bügel, Susanne; McGaw, Brian A.; Price, John; Reid, Martin D. (The Journal of nutrition, 2000)
Oat bran has a high phytate content and a low or inactivated phytase activity. A high intake of oat bran could therefore result in an impaired absorption of trace elements. The effect of a mean daily intake of 142 g of oat bran (102 g/10 MJ) on absorption of zinc was evaluated by the use of stable isotopes and fecal monitoring in 12 healthy subjects (6 males and 6 females). Each subject participated in two separate diet periods each of 21 d with identical low-fiber diets and with oat bran added in one of the periods. The oat bran was incorporated into bread and served at three daily main meals. The intake of zinc and phytate per 10 MJ was 138 μmol (9.0 mg) and 0.5 mmol, respectively, in the low-fiber period and 225 μmol (14.7 mg) and 4.0 mmol, respectively, in the oat bran period. Stable isotopes of zinc (70Zn) were added to the diets at d 7 of each period. The fractional absorptions (means ± sd) of zinc from the low-fiber and oat bran diets were 0.48 ± 0.11 and 0.40 ± 0.15 (P = 0.07), respectively. The higher zinc content in the oat bran period resulted in a greater amount of zinc absorbed (64 ± 19 μmol and 99 ± 51 μmol, respectively, P = 0.009). Balance data suggest that the higher absorbed amount of zinc resulted in correspondingly higher intestinal endogenous excretion of zinc. In conclusion, the absorption of zinc was high and not affected by addition of oat bran.